High quality H2-rich syngas production from pyrolysis-gasification of biomass and plastic wastes by Ni–Fe@Nanofibers/Porous carbon catalyst. (8th October 2019) - Zhang, Shuping; Zhu, Shuguang; Zhang, Houlei; Liu, Xinzhi; Xiong, Yuanquan
Abstract: To produce the high quality H2 -rich syngas from biomass and plastic wastes, a two-stage pyrolysis-gasification system involving pyrolysis and catalytic gasification is considered as a suitable route. Generally, synthesis of highly active, low cost and coke-resistant catalyst for tar cracking is the key factor. A series of monometallic catalysts of Ni@CNF/PCs and Fe@CNF/PCs and the bimetallic Ni–Fe@CNF/PCs catalyst were prepared by a simple one-step pyrolysis approach for high quality syngas production from pyrolysis-gasification of biomass and plastic wastes. The results indicated that the bimetallic Ni–Fe@CNF/PCs catalyst appeared as the optimal catalyst in affording the best compromise between catalytic activity and stability with the existence of the excellent dispersibility of the Fe0.64Ni0.36 alloy nanoparticles and the carbon nanofibers/porous carbon composite structure. In addition, the optimal operation conditions of biomass/plastic ratio of 1/2 and gasification temperature of 700 °C were observed for the bimetallic Ni–Fe@CNF/PCs catalyst to play best roles in the H2 -rich syngas quality, with up to 33.66 mmol H2 /g biomass, and tar yields as low as 5.66 mg/g. Graphical abstract: Image 1 Highlights: Pyrolysis-gasification process of biomass and plastic wastes was evaluated. Bimetallic Ni–Fe@CNF/PCs catalyst was prepared by one-step pyrolysis approach. Ni–Fe@CNF/PCs catalyst generated the highest yield and selectivity of H2 and CO. Ni–Fe@CNF/PCs catalyst was the optimal catalyst with high activity and stability.